Fractional derivative-based normalized viscoelastic model of strain-hardening clays - Tang, Yin; Wang, Peng; Ren, Peng; Zhang, Hua (Frontiers in Materials, 2024)
The stress-strain relationship of clays characterized by strain hardening exhibits varying curves under different confining pressures and dry densities. Considering the viscoelastic properties of clays, a normalized viscoelastic model of strain-hardening clay was established based on fractional derivatives, and normalization factors were proposed. Conventional triaxial shear tests under various dry density and confining pressure conditions were conducted on the clay from the Chengdu Universiade construction site. The experimental results showed that the stress-strain relationship of the clay was strain hardening. It shows that Chengdu clay has better normalization conditions. Furthermore, the normalized analysis of this clay through the viscoelastic normalization model revealed that the straight line of normalized data displayed a goodness-of-fit of over 0.98. The obtained values were consistent with experimental results, suggesting the reasonability of the normalized strain-hardening parameters and elastic moduli. In addition, the superiority of the developed model was verified by testing the strain-hardening clays in Wuhan, China and Bangkok, Thailand. After analyzing the strain-hardening parameters and normalization factors of our model, it was found that the slope of the normalized line can accurately reflect the strain-hardening ability of the clay. These findings demonstrated that the proposed normalization factor is preferred for a normalized viscoelastic model. It shows that the model proposed in this paper has clearer physical meaning and advancement.